The risk-incentive trade-off in competitive search - Onuchic, Paula Ferreira (2015)
I use the competitive search framework to model a job market with heterogeneous workers in which there is a moral hazard problem in the employer-worker relation. In this setting, I can predict how contracts react to changes in underlying parameters of the market (in particular, the production risk), as well as how the probability of each type of worker being hired responds. My main finding is that while at the individual level there is a negative risk- incentive trade-off, general equilibrium effects imply that the effect can be positive at the aggregate level depending on the market search frictions and the distribution of types. My re- sults help shed some light on some puzzling empirical findings on the risk-incentives trade-off.